Efektivitas Model Pembelajaran Quantum Learning dengan Media Aplikasi Bamboomedia Bmgames Apps Terhadap Keterampilan Membaca Permulaan Pada Siswa Kelas I MI Se-Kecamatan Kedungadem: The Effectiveness of Quantum Learning Learning Model with Bamboomedia Bmgames Apps Application Media on Beginning Reading Skills in Class I MI Students in Kedungadem District - Hasanudin, Cahyo; Asror, Abdul Ghoni (Pedagogia : Jurnal Pendidikan, 2017)
The aim of this study is to know whether applying quantum learning through Bamboomedia BMGames Apps or direct instruction using the book as a media which able to increase early reading skill. This study is under quasi experimental design that involves the first grade students of sixteen Madrasah Ibtidaiah in Kedungadem Residence. In deciding the sample the researcher used simple random sampling technique. The sample of the schools in this study were the first grade student of Madrasah Ibtidaiyah Muhammadiyah 1 Kedungadem as experimental class and the first grade of Madrasah Ibtidaiyah Muhammadiyah 27 Geger as control class. Data collection technique used were documentation and test. The result reveals that both of the group have a homogeneity variance (Fhitung = 0,0556 < 2,0879 = Ftabel) than using t test with significant level 0,05 reveals 7,0573 with t0,05;40 = 1,6838. From the t table DK = . tobs DK. Based on the data above, H0 is rejected. It can be concluded that the students taught using quantum learning collaborated with bamboomedia application have skill to read verb, and simple sentence better than the students taught using direct instruction using the book as media.